Prevalence of zoonotic parasites in feral cats of Central Virginia, USA. (25th June 2018) - Taetzsch, Sara J.; Gruszynski, Karen R.; Bertke, Andrea S.; Dubey, Jitender P.; Monti, Katelynn A.; Zajac, Anne M.; Lindsay, David S.
Abstract: Felis catus, the domestic cat, is the definitive host for parasites that may result in adverse health outcomes in humans. Prevalence data of zoonotic parasites in feral cats, which are free‐roaming domestic cats that are born and live in the wild, are limited. The objective of this study was to assess seroprevalence of Toxoplasma gondii antibodies and copro‐prevalence of potentially zoonotic parasites in feral cats and to evaluate risk factors for seropositivity and faecal excretion of parasites. In this cross‐sectional survey, 275 feral cats at Trap‐Neuter‐Release clinics in Central Virginia were tested for parasites via faecal flotation, direct immunofluorescence assay (faeces) and modified agglutination testing (serum). Toxoplasma gondii seroprevalence was 22.35% (95% CI: 17.47–27.86). Faecal prevalence of T. gondii ‐like oocysts was 1.04% (95% CI: 0.13–3.71), Toxocara cati 58.85% (95% CI: 51.54–65.89), Ancylostoma spp. 18.75% (95% CI: 13.49–25.00), Giardia duodenalis 5.73% (95% CI: 2.89–10.02) and Cryptosporidium spp. 3.33% (95% CI: 1.37–7.24). Female cats were more likely than males to excrete faecal Ancylostoma spp. eggs (OR 2.88; 95% CI 1.34–6.17). Adults were more likely than immature cats to be seropositive (OR 2.10; 95% CI: 1.11–3.97) and to excrete faecal Ancylostoma spp. eggs (OR 2.57; 95% CI: 1.10–5.99). However, immature cats were more likely than adults to excrete T. cati eggs (OR 6.79; 95% CI: 3.31–13.90) and to excrete one or more potentially zoonotic species (OR 4.67; 95% CI: 2.28–9.55) in faeces. Results of this study have implications for human and animal health and highlight the importance of collaboration between public health, medical and veterinary communities in preventive efforts.